BILATERAL RELATIONS, SECURITY AND MIGRATION: LEBANESE EXPATRIATES IN THE GULF STATES - Hourani, Guita (European Scientific Journal, ESJ, 2014)
Background: Lebanon is a source country of migration; it is an exporter of human resources, which goes mainly to the Gulf States. Given that the Gulf States’ bilateral relations with Lebanon have been deteriorating since the onset of the Syrian crisis, it is easy to see that there may be serious negative impacts on the wellbeing of the estimated 400,000 Lebanese expats in the Gulf States. In order to see if this is so, we conducted a survey of Lebanese working in the GCC, asking whether the weakening bilateral relations between the GCC and Lebanon was having a negative effect on their wellbeing. This research turns on the hypotheses that a), bilateral relations can be affected by population mobility and, in turn, that population mobility is affected by bilateral relations; b), when bilateral relations deteriorate between home and host countries, it negatively affects immigrants; and c), there is a clear correlation between bilateral relations and migrant wellbeing. Given the scarcity of data on residents and migrants in Lebanon, we explored our hypotheses using convenience sampling through social media, mainly Facebook and LinkedIn. Since Lebanese expatriates working in the Gulf countries are the ones most likely to be affected by the crisis, they were the focus of this research. To test the hypotheses, we used multiple methodologies and harnessed triangulated between literature on migrants, a media review, and our survey questionnaire. Our target population for the survey questionnaire consisted of all Lebanese working in the Gulf States. The questionnaire asked this cohort about their gender, religious affiliation and their origins by province in Lebanon; whether or not they were concerned over the deteriorating relations; whether they had made contingency plans should they be deported; and how they assessed the importance of the GCC to Lebanon. By triangulating with the literature and media review, we used our responses to obtain additional insights and relevant contextual information. In conclusion, we offer three findings: a) When bilateral relations deteriorate between home and host countries, it negatively affects immigrants; b) There is a clear correlation between bilateral relations and migrant wellbeing; and c) Bilateral relations can be affected by population mobility and, in turn, that population mobility is affected by bilateral relations. Given these findings, we claim that Lebanon urgently needs to devise a policy that protects its long-term interest with the GCC and to formulate a comprehensive national emigration policy. Lebanon is distinguished by the high degree of skilled human capital it generates and exports, accounting for one quarter of its Gross Domestic Product. Given the size and importance of this factor, Lebanon should therefore deal wisely with the situation before it metastasizes.